2013
DOI: 10.1111/j.1755-3768.2013.2254.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for clinical outcomes in patients with Vogt‐Koyanagi‐Harada disease treated with high‐dose corticosteroids

Abstract: Purpose: To determine prognostic factors in patients with Vogt‐Koyanagi‐Harada (VKH) disease who were treated with high‐dose corticosteroids. Methods: Analysis of 87 patients (174 eyes). Results: Chronic recurrent presentation was significantly associated with more severe anterior segment inflammation at presentation as indicated by presence of mutton‐fat keratic precipitates, anterior chamber reaction of 2+ or more, iris nodules and posterior synechiae, less exudative retinal detachment at presentation, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…[1][2][3][4][5][6] While corticosteroids are the mainstay of therapy and are required to control active inflammation during episodes of acute or recurrent inflammation, cumulative evidence supports the first-line use of corticosteroid-sparing immunosuppressive agents to reduce the risk of recurrence, decrease the development of late complications, and improve long-term vision. [16][17][18][19][20] Multimodal imaging studies, particularly fluorescein angiography and spectral domain-ocular coherence tomography (SD-OCT), are important adjuncts for initial diagnosis and early monitoring of treatment response. 5 Indocyanine green angiography (ICGA) appears to be especially useful for detecting suboptimal or incomplete control of choroidal inflammation in patients with longstanding or chronic/recurrent disease.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] While corticosteroids are the mainstay of therapy and are required to control active inflammation during episodes of acute or recurrent inflammation, cumulative evidence supports the first-line use of corticosteroid-sparing immunosuppressive agents to reduce the risk of recurrence, decrease the development of late complications, and improve long-term vision. [16][17][18][19][20] Multimodal imaging studies, particularly fluorescein angiography and spectral domain-ocular coherence tomography (SD-OCT), are important adjuncts for initial diagnosis and early monitoring of treatment response. 5 Indocyanine green angiography (ICGA) appears to be especially useful for detecting suboptimal or incomplete control of choroidal inflammation in patients with longstanding or chronic/recurrent disease.…”
mentioning
confidence: 99%
“…It is considered a primary stromal choroiditis because the inflammatory reaction electively starts within the choroidal stroma [9]. The initial-onset acute disease typically exhibits granulomatous choroiditis with exudative retinal detachment and optic disk hyperemia and swelling, followed by anterior segment involvement and eventual development into chronic recurrent granulomatous anterior uveitis if not properly treated, with typical ''sunset glow fundus'' (SGF) and chorioretinal atrophy [10][11][12][13].…”
mentioning
confidence: 99%
“…This early stage of disease represents the therapeutic window of opportunity, during which the disease is amenable to appropriate therapeutic intervention. If the window closes without sufficient treatment, evolution will irremediably progress toward chronic disease (smoldering or recurrent) which is much more refractory to treatment and needs prolonged and repeated therapeutic intervention [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the need for more aggressive treatment in our patients with late relapses of VKH may be a marker of more severe disease. Early corticosteroid-sparing immunomodulatory therapy might be useful as first-line therapy to reduce the development of complications (Abu El-Asrar et al 2013). Although it is difficult to conclude because we do not have enough statistical power (tests of Kaplan-Meier), we observed that subjects who had a longer duration of high dose corticosteroids (>3 months) at presentation of the disease were more likely to present posterior segment reactivation than those with shorter duration of corticosteroids therapy (This comparison raises the issue of resistance to corticosteroids treatment (and/or resistance to immunosuppressive therapies), of various therapeutics.…”
mentioning
confidence: 99%